Initial Preference for Labor Without Neuraxial Analgesia and Actual Use: Results From a National Survey in France. Issue 2 (April 2016) - Kpéa, Laure; Bonnet, Marie-Pierre; Le Ray, Camille; Prunet, Caroline; Ducloy-Bouthors, Anne-Sophie; Blondel, Béatrice
Abstract : Surv Anesthesiol 2016;60(2):63–64 Use of analgesia (eg, epidural, spinal, or combined spinal-epidural) during caesarean delivery is common and effective and should, in principle, always be the women's choice. However, few studies have examined the discordance between a woman's initial preference to not use neuraxial analgesia and its actual final use.